2020
DOI: 10.13106/jafeb.2020.vol7.no9.241
|View full text |Cite
|
Sign up to set email alerts
|

FDI, Corruption and Development of Public Service Sectors in ASEAN Countries

Abstract: This study aims to empirically examine the effect of foreign direct investment (FDI) and corruption on the development of public-service sectors in 10 ASEAN countries. It then investigates whether this relationship is different between two FDI compositions including greenfield FDI and FDI in the form of cross-border merger and acquisitions (M&As). Using a panel database of 10 ASEAN countries during the period 1996-2015 from various sources including the World Development Indicators of the World Bank and UNCTAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The empirical literature on the relationship between FDI inflows and environmental degradation have reached mixed consequences. [ [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] ], have uncovered that FDI inflows increased the environmental degradation, but [ [54] , [55] , [56] ] discovered that FDI inflows fostered the environmental improvement. However [ 8 , 57 ], have been concluded that the effects of FDIs on environmental degradation are different in the short and long term [ 58 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The empirical literature on the relationship between FDI inflows and environmental degradation have reached mixed consequences. [ [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] ], have uncovered that FDI inflows increased the environmental degradation, but [ [54] , [55] , [56] ] discovered that FDI inflows fostered the environmental improvement. However [ 8 , 57 ], have been concluded that the effects of FDIs on environmental degradation are different in the short and long term [ 58 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, an inverted U-shaped relationship was found between FDI and CO 2 emissions for the Asian sub-panel. [ 50 ] System generalized moment method (system-GMM) FDIs have a positive effect on environmental pollution. [ 51 ] Multivariate regression model There was evidence of the existence of the pollution haven hypothesis in the Balkans, while the EKC hypothesis was rejected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sources of funds include all net official inflows (increase in public sector net external debt) and net flows of foreign direct investment. Users of funds include current account deficits and changes in foreign exchange reserves (Phan and Nguyen, 2020). Capital flight out occurs when the source of funds exceeds the use of funds and vice versa for the flight of capital in, so that the residuals of both are indicated as outward or inward capital flights.…”
Section: Literature Reviewmentioning
confidence: 99%